A zirconate-based pure red up-conversion luminescent material and preparation method thereof
Zirconate-based pure red upconversion luminescent material prepared by erbium ion doping solves the problem of low color purity and difficult to be excited by 1550nm in the existing Er3+ doped materials, and achieves high color purity and good temperature response red top purity Convert the luminous effect.
Patent Information
- Application Number
- CN202310853675.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-12
AI Technical Summary
The existing Er3+ doped red upconverting luminescent materials have low color purity and are not easily stimulated effectively by 1550nm excitation.
Zirconate-based pure red upconverting luminescent material was prepared by erbium ion doping. The chemical formula is Yb0.2(1-x)Zr0.8O1.9:xEr3+, where 0
It is achieved that pure red upconversion luminescence can be obtained under excitation of 980nm and 1550nm, with pure redness, maximum color purity reaching 95.83% and 99.92%, respectively, and good temperature response sensitivity.
Smart Images

Figure CN117025219B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid luminescent materials, and in particular to a zirconate-based pure red up-conversion luminescent material and a preparation method thereof. Background Art
[0002] Red upconversion luminescent material is a fluorescent material that can convert near-infrared light into visible light. Its characteristic is that the energy of the emitted photons is greater than the energy of the absorbed photons, which is an anti-Stokes phenomenon.
[0003] Rare earth ion doped upconversion luminescent materials have been widely used in lasers, displays, fluorescent anti-counterfeiting, bio-imaging, optical temperature measurement, etc. due to their excellent properties such as stable physical and chemical properties and tunable luminescent colors. 3+ Because it can be effectively excited by 980nm infrared light, Er in upconversion luminescent materials 3+ Often serves as a luminous center.
[0004] Because Er 3+ The special energy level structure has multiple energy level transition pathways and easily produces upconversion luminescence with impure luminescence color. Therefore, how to obtain pure red upconversion luminescence is a key difficulty.
[0005] And because of Er 3+ The red up-conversion luminescence band of Er is just in the first optical window of biological tissue (650-900nm). Biological tissue has low absorption and high transmittance in this band. This characteristic makes Er 3+ Doped red upconversion luminescent materials have great application value in biological imaging. Fluorescence bioimaging technology uses fluorescent materials to be highly sensitive to the local environment to form images. In recent years, due to the development of 1550nm excitation sources located in the third window of optical communication, 1550nm lasers have the unique advantages of eye safety, low cost, and easy integration with small silicon-based optoelectronic devices compared to 980nm lasers. Therefore, the development of pure red upconversion luminescent materials under 1550nm excitation is of great value in the field of biological tissue cell temperature monitoring. Summary of the invention
[0006] Aiming at the existing technology 3+ The doped red up-conversion luminescent material has low color purity and is not easily effectively excited by 1550nm. The purpose of the present invention is to provide a zirconate-based pure red up-conversion luminescent material and a preparation method thereof. By doping erbium ions, a zirconate-based red up-conversion luminescent material with good stability, high color purity and high temperature response sensitivity is obtained to meet its application requirements in the fields of biological imaging and temperature measurement.
[0007] In order to achieve the above object, the technical solution of the present invention is: a zirconate-based pure red up-conversion luminescent material, the chemical formula of the zirconate-based pure red up-conversion luminescent material is: Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+ , where 0 <x≤0.50。
[0008] Furthermore, the zirconate-based pure red up-conversion luminescent material obtains red up-conversion luminescence around 600-750nm under 980nm laser irradiation.
[0009] Furthermore, the zirconate-based pure red up-conversion luminescent material obtains red up-conversion luminescence around 600-750nm under 1550nm laser irradiation.
[0010] Further, under the irradiation of 980nm laser, the ratio of the maximum luminous intensity of the red up-conversion luminescence to the minimum luminous intensity of the zirconate-based pure red up-conversion luminescent material can reach 26.74. Further, under the irradiation of 980nm laser, the ratio of the maximum luminous intensity of the red up-conversion luminescence to the minimum luminous intensity of the zirconate-based pure red up-conversion luminescent material is 3.33-26.74.
[0011] Furthermore, under 1550nm laser irradiation, the ratio of the maximum luminous intensity of the red upconversion luminescence to the minimum luminous intensity of the zirconate-based pure red upconversion luminescent material can reach 189.98. Furthermore, the ratio of the maximum luminous intensity of the red upconversion luminescence to the minimum luminous intensity is 2.05-189.98.
[0012] The present invention utilizes the luminescent color purity formula:
[0013] Among them, I R and I G They represent the red and green light emission intensities of the material, respectively, and quantitatively characterize the red light color purity of the sample.
[0014] Furthermore, the color purity of the zirconate-based pure red up-conversion luminescent material under 980nm laser irradiation can reach 95.83%. Furthermore, the color purity of the zirconate-based pure red up-conversion luminescent material under 980nm laser irradiation can reach 87.92-95.83%.
[0015] Furthermore, the color purity of the zirconate-based pure red up-conversion luminescent material can reach 99.92% under 1550nm laser irradiation. Furthermore, the color purity of the red light of the zirconate-based pure red up-conversion luminescent material can reach 98.29-99.92% under 1550nm laser irradiation.
[0016] Furthermore, under 980nm laser irradiation, the zirconate-based pure red up-conversion luminescent material emits red light at 647nm and emits red light at 656nm, and the intensity ratio of the two is quantitatively related to the temperature:
[0017] Where I represents the integrated luminous intensity, k B , T and ΔE represent the Boltzmann constant, absolute temperature and the energy difference between two thermal bonding levels, respectively. The subscripts “up” and “low” represent 4F 9 / 2 The energy level is split at 647 nm and the energy level is split at 656 nm. up with I low The ratio of (Iup / Ilow) .
[0018] Furthermore, the zirconate-based pure red up-conversion luminescent material has a maximum absolute sensitivity of 0.24% K-1 under 980 nm laser irradiation. 1 , the maximum relative sensitivity is 0.45% K- 1 .
[0019] In order to achieve the above object, the present invention also provides: a method for preparing a zirconate-based pure red up-conversion luminescent material, comprising the following steps:
[0020] S1: Preset the mass of the target product, and weigh the Yb source, Zr source and Er source containing O element as raw materials according to the chemical formula of the zirconate-based pure red up-conversion luminescent material;
[0021] S2: Mixing and grinding the raw material and the co-solvent obtained in step S1 uniformly under ethanol conditions;
[0022] S3: placing the mixture obtained in step S2 in a muffle furnace for high-temperature sintering in air to obtain a target product.
[0023] Furthermore, in step S3, the high temperature sintering is staged high temperature sintering.
[0024] Furthermore, in step S3, the specific method of high temperature sintering is: first calcining at 1350-1450°C for 1-3h, and then calcining at 1500-1600°C for 4-8h.
[0025] Furthermore, during the high temperature sintering process, the furnace temperature is first raised to 1350-1450°C for calcination within 2-3 hours, and then further raised to 1500-1600°C within 0.5-1.5 hours.
[0026] Furthermore, in step S3, after high-temperature sintering, the temperature is lowered at a rate of 4-6°C / min to 400-600°C, and then naturally cooled.
[0027] Furthermore, the Yb source containing the O element is ytterbium oxide; the Zr source containing the O element is zirconium oxide; and the Er source containing the O element is erbium oxide.
[0028] In summary, the present invention has the following beneficial effects:
[0029] First, the erbium ion-doped zirconate-based red up-conversion material of the present invention can obtain pure red up-conversion luminescence under 980 nm and 1550 nm excitation, with pure red color and the highest color purity reaching 95.83% and 99.92% respectively;
[0030] Second, when the red up-conversion material prepared in the present application is excited at 980 nm, the intensity ratio of the two red light emission peaks changes regularly with the change of temperature, and the equation related to the fluorescence intensity ratio and temperature is fitted. This temperature measurement method has good temperature response sensitivity and has broad application prospects in the fields of biological imaging and temperature measurement.
[0031] Third, the present application adopts a high-temperature solid-phase method to prepare red upconversion materials, which has a simple process, low equipment cost, easy operation, no environmental pollution, short preparation cycle, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0033] Figure 1 X-ray diffraction patterns of Examples 1, 3, 5, 7, 9, and 11 of the present invention;
[0034] Figure 2 is the up-conversion emission spectrum of the materials in Examples 1-11 of the present invention under 980nm excitation;
[0035] Figure 3 is the up-conversion emission spectrum of the material in Examples 1-11 of the present invention under 1550nm excitation;
[0036] Figure 4 It is the up-conversion emission spectra of the materials in Example 9 of the present invention and Comparative Examples 1 and 2 under 980nm excitation;
[0037] Figure 5 The up-conversion emission spectra of the materials in Example 9 and Comparative Examples 1 and 2 under 1550nm excitation;
[0038] Figure 6 The up-conversion emission spectra of the material in Example 9 of the present invention at different temperatures measured under 980nm excitation, the temperature range is 303-723K, and the temperature interval is 30K;
[0039] Figure 7 The relationship between the integral area of the emission peak corresponding to the red luminescence-related transition and the temperature of the material in Example 9 of the present invention under 980nm excitation;
[0040] Figure 8 is the fluorescence intensity ratio calculated based on the variable temperature up-conversion emission spectrum of the material in Example 9 of the present invention, and the relationship equation between the fluorescence intensity ratio and the temperature obtained by fitting;
[0041] Fig. 9 is the absolute sensitivity S of the temperature response of the red fluorescence temperature measurement of the material in Example 9 of the present invention A and relative sensitivity S R . DETAILED DESCRIPTION
[0042] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the following will be combined with the appended drawings of the embodiments of the present invention. Figure 1-9 The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.
[0043] Example
[0044] Embodiment 1:
[0045] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+The stoichiometric ratio of the elements in the experiment was 0.01, where x was 0.01. 0.8483 g of Yb2O3, 2.1219 g of ZrO2, 0.0083 g of Er2O3 and 0.3000 g of H3BO3 were weighed respectively. All the above materials were placed in an agate mortar, and then an appropriate amount of alcohol was added to just cover the powder mixture. The purpose of adding alcohol is to provide a liquid environment so that the mixture can be more easily mixed. After mixing, it was fully ground for 30 minutes. After mixing evenly, the mixture was transferred to a crucible, and then the crucible was placed in a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400°C after 2.5 hours of heating process, and it is kept warm for 2 hours. Then, it is heated from 1400°C to 1550°C after 1 hour, and it is kept warm for 6 hours. Then, it is cooled from 1550°C to 500°C at a cooling rate of 5°C / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain a phosphor material.
[0046] Embodiment 2:
[0047] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+ The stoichiometric ratio of the elements in the formula is x=0.03. Weigh 0.8311g Yb2O3, 2.1219g ZrO2, 0.0250g Er2O3, and 0.3000g H3BO3 respectively, put them in an agate mortar, add appropriate amount of alcohol and grind them thoroughly for 30 minutes, transfer them into a crucible after mixing evenly, and put the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400℃ after 2.5h of heating process, and the temperature is kept for 2h, and then the temperature is raised from 1400℃ to 1550℃ after 1h, and the temperature is kept for 6h, and then the temperature is lowered from 1550℃ to 500℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0048] Embodiment 3:
[0049] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+The stoichiometric ratio of the elements in the formula is x=0.05. Weigh 0.8140g Yb2O3, 2.1219g ZrO2, 0.0416g Er2O3, and 0.3000g H3BO3, place them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes. After mixing evenly, transfer them into a crucible, and place the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400℃ after 2.5h of heating process, and the temperature is kept for 2h. Then, the temperature is raised from 1400℃ to 1550℃ after 1h, and the temperature is kept for 6h. Then, the temperature is lowered from 1550℃ to 500℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0050] Embodiment 4:
[0051] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+ The stoichiometric ratio of the elements in the formula is x=0.07. Weigh 0.7969g Yb2O3, 2.1219g ZrO2, 0.0582g Er2O3, and 0.3000g H3BO3, place them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes. After mixing evenly, transfer them into a crucible, and place the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400°C after 2.5 hours of heating process, and the temperature is kept for 2 hours. Then, the temperature is raised from 1400°C to 1550°C after 1 hour, and the temperature is kept for 6 hours. Then, the temperature is lowered from 1550°C to 500°C at a cooling rate of 5°C / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0052] Embodiment 5:
[0053] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+The stoichiometric ratio of the elements in the formula is x=0.10. Weigh 0.7712g Yb2O3, 2.1219g ZrO2, 0.0832g Er2O3, and 0.3000g H3BO3, place them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes. After mixing evenly, transfer them into a crucible, and place the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400°C after 2.5 hours of heating process, and the temperature is kept for 2 hours. Then, the temperature is raised from 1400°C to 1550°C after 1 hour, and the temperature is kept for 6 hours. Then, the temperature is lowered from 1550°C to 500°C after 210 minutes, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0054] Embodiment 6:
[0055] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+ The stoichiometric ratio of the elements in the formula is x=0.15. Weigh 0.7283g Yb2O3, 2.1219g ZrO2, 0.1248g Er2O3, and 0.3000g H3BO3, place them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes. After mixing evenly, transfer them into a crucible, and place the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400°C after 2.5 hours of heating process, and the temperature is kept for 2 hours. Then, the temperature is raised from 1400°C to 1550°C after 1 hour, and the temperature is kept for 6 hours. Then, the temperature is lowered from 1550°C to 500°C at a cooling rate of 5°C / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0056] Embodiment 7:
[0057] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+The stoichiometric ratio of the elements in the formula is x=0.20. Weigh 0.6855g Yb2O3, 2.1219g ZrO2, 0.1663g Er2O3, and 0.3000g H3BO3 respectively, put them in an agate mortar, add appropriate amount of alcohol and grind them thoroughly for 30 minutes, transfer them into a crucible after mixing evenly, and put the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400℃ after 2.5h of heating process, and the temperature is kept for 2h, and then the temperature is raised from 1400℃ to 1550℃ after 1h, and the temperature is kept for 6h, and then the temperature is lowered from 1550℃ to 500℃ at a cooling rate of 5℃ / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0058] Embodiment 8:
[0059] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+ The stoichiometric ratio of the elements in the formula is x=0.25. Weigh 0.6426g Yb2O3, 2.1219g ZrO2, 0.2079g Er2O3, and 0.3000g H3BO3, place them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes. After mixing evenly, transfer them into a crucible, and place the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400°C after 2.5 hours of heating process, and the temperature is kept for 2 hours. Then, the temperature is raised from 1400°C to 1550°C after 1 hour, and the temperature is kept for 6 hours. Then, the temperature is lowered from 1550°C to 500°C at a cooling rate of 5°C / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0060] Embodiment 9:
[0061] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+The stoichiometric ratio of the elements in the formula is x=0.30. Weigh 0.5998g Yb2O3, 2.1219g ZrO2, 0.2495g Er2O3, and 0.3000g H3BO3, place them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes. After mixing evenly, transfer them into a crucible, and place the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400°C after 2.5 hours of heating process, and the temperature is kept for 2 hours. Then, the temperature is raised from 1400°C to 1550°C after 1 hour, and the temperature is kept for 6 hours. Then, the temperature is lowered from 1550°C to 500°C at a cooling rate of 5°C / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0062] Embodiment 10:
[0063] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+ The stoichiometric ratio of the elements in the formula is x=0.40. Weigh 0.5141g Yb2O3, 2.1219g ZrO2, 0.3327g Er2O3, and 0.3000g H3BO3, place them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes. After mixing evenly, transfer them into a crucible, and place the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400°C after 2.5 hours of heating process, and the temperature is kept for 2 hours. Then, the temperature is raised from 1400°C to 1550°C after 1 hour, and the temperature is kept for 6 hours. Then, the temperature is lowered from 1550°C to 500°C at a cooling rate of 5°C / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain a phosphor material.
[0064] Embodiment 11:
[0065] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+The stoichiometric ratio of the elements in the formula is x=0.50. Weigh 0.4284g Yb2O3, 2.1219g ZrO2, 0.4159g Er2O3, and 0.3000g H3BO3, place them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes. After mixing evenly, transfer them into a crucible, and place the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400°C after 2.5 hours of heating process, and the temperature is kept for 2 hours. Then, the temperature is raised from 1400°C to 1550°C after 1 hour, and the temperature is kept for 6 hours. Then, the temperature is lowered from 1550°C to 500°C at a cooling rate of 5°C / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0066] Comparative Example
[0067] Comparative Example 1
[0068] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+ The stoichiometric ratio of the elements in the formula, where x=0, weigh 0.8568g Yb2O3, 2.1219g ZrO2, and 0.3000g H3BO3, respectively, put them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes, transfer them into a crucible after mixing evenly, and put the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature to 1400℃ after 2.5h of heating process, keep it warm for 2h, then heat from 1400℃ to 1550℃ after 1h, keep it warm for 6h, then cool from 1550℃ to 500℃ at a cooling rate of 5℃ / min, and then cool naturally to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0069] Comparative Example 2
[0070] The preset target product mass is 3.000g. According to the chemical expression Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+The stoichiometric ratio of the elements in the formula is x=0.80. Weigh 0.1714g Yb2O3, 2.1219g ZrO2, 0.6654g Er2O3, and 0.3000g H3BO3, place them in an agate mortar, add an appropriate amount of alcohol and grind them thoroughly for 30 minutes. After mixing evenly, transfer them into a crucible, and place the crucible into a muffle furnace for high-temperature sintering. The specific heating process is as follows: from room temperature, the temperature reaches 1400°C after 2.5 hours of heating process, and the temperature is kept for 2 hours. Then, the temperature is raised from 1400°C to 1550°C after 1 hour, and the temperature is kept for 6 hours. Then, the temperature is lowered from 1550°C to 500°C at a cooling rate of 5°C / min, and then naturally cooled to room temperature. The sample is taken out and ground into powder to obtain the phosphor material.
[0071] The luminescence performance of the phosphor materials provided in the above Examples 1-11 was tested using a F4600 fluorescence spectrometer produced by Hitachi. The luminescence performance of the materials under excitation at 980nm and 1550nm was tested respectively, and the luminescence color purity was calculated using the following formula. The calculation results are shown in Table 1.
[0072] Luminous color purity formula:
[0073] Among them, I R and I G They represent the red and green light emission intensities of the material, respectively, and quantitatively characterize the red light color purity of the sample.
[0074] Table 1 Red light color purity of phosphor materials provided in Examples 1-11
[0075]
[0076] It can be seen from Table 1 that the red light color purity of the sample under 1550nm excitation is higher than that under 980nm excitation. 3+ With the increase of concentration, the red light purity increases first and then decreases; under 1550nm excitation, with the increase of Er 3+ With the increase of concentration, the color purity of red light does not change significantly, and basically maintains at a high level. Under 980nm and 1550nm excitation, the color purity of red light reaches 95.83% and 99.92% respectively.
[0077] Figure 1 The X-ray diffraction patterns of the phosphor materials prepared in Examples 1, 3, 5, 7, 9 and 11 show that the prepared Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+ The material is a single-phase material, no other impurity phases are produced, and the crystallinity is good.
[0078] Figure 2 The up-conversion emission spectrum of the phosphor material prepared in Example 1-11 under 980nm excitation;
[0079] Figure 3 The up-conversion emission spectra of the samples prepared in Example 1-11 under 1550nm excitation;
[0080] Combination Figure 2-3 It can be seen that under the excitation of 980nm and 1550nm, the main emission peaks of the phosphor materials are around 600-750nm, which is red up-conversion luminescence.
[0081] Figure 4 The up-conversion emission spectra of the phosphor materials prepared in Comparative Examples 1, 2 and Example 9 under 980nm excitation;
[0082] Figure 5 The up-conversion emission spectra of the phosphor materials prepared in Comparative Examples 1, 2 and Example 9 under 1550nm excitation;
[0083] Combination Figure 4-5 It can be seen that under 980nm excitation, the red luminescence intensity of the phosphor materials prepared in Comparative Examples 1 and 2 is weaker than the red luminescence intensity of the phosphor material prepared in Example 9; under 1550nm excitation, the red luminescence intensity of the phosphor material prepared in Comparative Example 1 is weaker than that of the phosphor material prepared in Example 9. Although the red luminescence intensity of the phosphor material prepared in Comparative Example 2 is stronger than that of the phosphor material prepared in Example 9, the green luminescence intensity of the sample in Comparative Example 2 also accounts for a considerable proportion, and the monochromaticity is worse than that of the sample in Example 9.
[0084] Figure 6 The up-conversion emission spectra of the phosphor material prepared in Example 9 under 980nm excitation and at different temperature conditions;
[0085] Depend on Figure 6 It can be seen that when the temperature interval is 30K, it can be seen that the red luminous intensity of the phosphor material decreases with the increase of temperature, and the green luminous intensity does not change much with temperature.
[0086] Figure 7 Given Figure 4 Under 980nm laser irradiation, the red luminescence integrated intensity (I 647 ) and the red luminescence integrated intensity at 656nm (I 656 ) and the sum of the two intensities with temperature. It can be seen that the integrated intensity of the three decreases with increasing temperature, which is the temperature quenching effect. Generally speaking, as the temperature increases, 4 F 9 / 2The probability of non-radiative relaxation of particles occupying the energy level increases, resulting in a decrease in luminescence intensity.
[0087] Figure 8 Given Figure 4 The relationship between the red luminescence intensity ratio at 647nm and the red luminescence intensity at 656nm and temperature under 980nm laser irradiation is shown in the figure, where the solid line is the formula:
[0088] The fitting results are as follows, where I represents the integrated luminescence intensity, k B , T and ΔE represent the Boltzmann constant, absolute temperature and the energy difference between the two thermal bonding levels, respectively. The subscripts “up” and “low” represent 4 F 9 / 2 The splitting sublevel at 647nm and 4 F 9 / 2 The energy level is split at 656nm, and I up with I low The ratio of (Iup / Ilow) .
[0089] Depend on Figure 8 It can be seen that the red light intensity at 647nm is FIR compared to the red light intensity at 656nm. (I647 / I656) It changes regularly with increasing temperature.
[0090] Fig. 9 Given Figure 6 Under 980nm laser irradiation, the absolute and relative sensitivity of temperature response (S A and S R ) and temperature, and is calculated using the following formula:
[0091]
[0092]
[0093] Depend on Fig. 9 It can be seen that the absolute sensitivity S of the temperature measurement mode based on the red light emission fluorescence intensity ratio is calculated A and relative sensitivity S R , the maximum value is 0.24%K -1 and 0.45% K -1 It is found that the temperature sensing sensitivity of the phosphor material prepared in the present application increases as the temperature decreases, and thus the phosphor material prepared in the present application can have good temperature response characteristics at room temperature and below.
[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A zirconate-based pure red upconversion luminescent material, characterized in that: The general chemical formula of the zirconate-based pure red up-conversion luminescent material is: Yb 0.2(1-x) Zr 0.8 O 1.9 :xEr 3+ , where x represents Er 3+ The doping amount of Yb 3+ The percentage of doping amount, 0 <x≤0.50。 2. A zirconate-based pure red up-conversion luminescent material according to claim 1, characterized in that: The zirconate-based pure red up-conversion luminescent material obtains red up-conversion luminescence at around 600-750nm under 980nm laser irradiation; When the zirconate-based pure red up-conversion luminescent material is irradiated by a 980nm laser, the ratio of the maximum luminous intensity of the red up-conversion luminescence to the minimum luminous intensity can reach 26.
74.
3. The zirconate-based pure red up-conversion luminescent material according to claim 1, characterized in that: The zirconate-based pure red up-conversion luminescent material obtains red up-conversion luminescence at around 600-750nm under 1550nm laser irradiation; When the zirconate-based pure red up-conversion luminescent material is irradiated by a 1550nm laser, the ratio of the maximum luminous intensity of the red up-conversion luminescence to the minimum luminous intensity can reach 189.
98.
4. The zirconate-based pure red up-conversion luminescent material according to claim 1, characterized in that: The zirconate-based pure red up-conversion luminescent material can achieve a red light purity of 95.83% under 980nm laser irradiation; The zirconate-based pure red up-conversion luminescent material can achieve red light purity of 99.92% under 1550nm laser irradiation.
5. The zirconate-based pure red up-conversion luminescent material according to claim 1, characterized in that: The zirconate-based pure red up-conversion luminescent material emits red light at 647 nm and red light at 656 nm under 980 nm laser irradiation, and the intensity ratio of the two is quantitatively related to the temperature: Where I represents the integrated luminous intensity, A is a constant, and k B represents the Boltzmann constant; T represents the absolute temperature; ΔE represents the energy difference between two thermally coupled energy levels, and the subscripts up and low of I refer to the previous energy level and the next energy level, respectively, corresponding to 4 F 9 / 2 The energy levels are the splitting sublevel at 647nm and the splitting sublevel at 656nm.
6. The zirconate-based pure red up-conversion luminescent material according to claim 1, characterized in that: The zirconate-based pure red up-conversion luminescent material has a maximum absolute sensitivity of 0.24% K for temperature sensing under 980nm laser irradiation. -1 , the maximum relative sensitivity is 0.45%K -1 .
7. A method for preparing a zirconate-based pure red up-conversion luminescent material according to any one of claims 1 to 6, characterized in that: The steps include: S1: Preset the mass of the target product, and weigh the Yb source, Zr source and Er source containing O element as raw materials according to the chemical formula of the zirconate-based pure red up-conversion luminescent material; S2: Mixing and grinding the raw material and the co-solvent obtained in step S1 uniformly under ethanol conditions; S3: placing the mixture obtained in step S2 in a muffle furnace under air atmosphere for high temperature sintering to obtain a target product; Wherein, the cosolvent is boric acid H3BO3; The specific method of high temperature sintering is: first calcining at 1350-1450°C for 1-3h, and then calcining at 1500-1600°C for 4-8h.
8. The method for preparing a zirconate-based pure red up-conversion luminescent material according to claim 7, characterized in that: In step S3, after high-temperature sintering, the temperature is lowered at a rate of 4-6°C / min to 400-600°C, and then naturally cooled.
9. The method for preparing a zirconate-based pure red up-conversion luminescent material according to claim 7, characterized in that: The Yb source containing the O element is ytterbium oxide; the Zr source containing the O element is zirconium oxide; and the Er source containing the O element is erbium oxide.